2010
DOI: 10.1183/09031936.00032310
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and COPD affect different domains of nutritional status: the ECCE study

Abstract: Chronic obstructive pulmonary disease (COPD) and ageing may contribute to malnutrition. We aimed to explore whether COPD and ageing determine malnutrition in different manners.460 stable COPD outpatients (376 males and 84 females) from the Extrapulmonary Consequences of COPD in the Elderly (ECCE) study database were investigated (age 75.0¡5.9 yrs; forced expiratory volume in 1 s 54.7¡18.3% predicted). Nutritional status was evaluated using the Mini Nutritional Assessment1 (MNA) questionnaire. From the MNA, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 41 publications
3
21
0
7
Order By: Relevance
“…Several assessment tools of nutritional depletion for patients with COPD, such as questionnaire (mini-nutritional assessment, MNA 28 ; subjective global assessment, SGA 29 ) and body weight, have already been reported. The GNRI is easier to use than the MNA and is not based on subjective judgment as is the SGA.…”
Section: Discussionmentioning
confidence: 99%
“…Several assessment tools of nutritional depletion for patients with COPD, such as questionnaire (mini-nutritional assessment, MNA 28 ; subjective global assessment, SGA 29 ) and body weight, have already been reported. The GNRI is easier to use than the MNA and is not based on subjective judgment as is the SGA.…”
Section: Discussionmentioning
confidence: 99%
“…Its aetiology is multifactorial; however, inadequate oral intake is one of the identified causes [125,126]. Obase et al [127] reported that daily iron intake among 13 COPD patients was about half of that of 27 age-matched controls; however, literature data on mineral intake among COPD patients are limited, so the frequency and severity of true iron deficiency as a cause of anaemia cannot be accurately estimated.…”
Section: Nutritionmentioning
confidence: 97%
“…The cause of anaemia is multifactorial. Increased systemic inflammatory markers, such as TNF-α and IL-6 [132,133], decreased sensitivity of erythroid progenitor cells to EPO [134], lower ability of the aging kidney to produce adequate EPO quantities [131], malnutrition [126] and high burden of co-morbidities [130,131] all contribute to the establishment of anaemia in the elderly.…”
Section: Agingmentioning
confidence: 99%
“…Additionally, COPD and aging are independent and probably concurrent conditions leading to malnutrition. Recent evidence suggests that COPD influences aspects related to body composition, whereas both COPD and aging contribute to poor body functionality [30]. Finally, the combination of nutritional supplementation with low-intensity exercise training may help to increase weight and energy intake, as well as exercise capacity and health-related quality of life in elderly malnourished COPD patients [31].…”
Section: Nonpharmacologic Interventionsmentioning
confidence: 99%